Phonetic variation and change in the Cockney Diaspora: The role of place, gender, and identity. (November 2021) - Cole, Amanda; Evans, Bronwen G.
Abstract: Recent research has suggested that two linguistic processes are displacing Cockney: the emergence of Multicultural London English (MLE) in inner London and dialect levelling (e.g. Kerswill & Williams 2005 ). This study investigates firstly whether Cockney phonetic features have 'moved East' to Essex (Fox 2015 ), and secondly the features' indexicality in relation to place and identity. Fifty-four participants from Debden, an outpost of the Cockney Diaspora, completed a sociolinguistic interview. Vowel measurements were made from a wordlist and passage, and quantitative attitudinal and qualitative data were extracted from a questionnaire and interviews. Overall, changes in identity as a result of social change exceeded linguistic changes, and linguistic labels were not interpreted uniformly across the community. Whilst Cockney variants were largely maintained in young speakers, they were transposed onto an 'Essex' accent. Furthermore, some young women but no young men considered themselves Cockney, likely due to the matrifocal nature of Cockney. (Cockney, phonetic variation and change, dialect levelling, identity, indexicality, gender)